First experimental values for the light penetration depth of platinum and iron gases at 532 nm - Prieto, Gonzalo Rodríguez (2020)
Light penetration depth is a fundamental property that has been researched extensively with a large amount of materials. Among those studies, different planetary atmospheres and material phases, like plasmas, had been previously addressed, both theoretically and experimentally. However, no experimental data are available for platinum and iron gases due to the difficulties for the creation of gas state from a solid metal material. This work present experimental penetration depths at 532 nm laser light for iron and platinum gases produced by a carefully tuned exploding wire system in atmospheric air. Iron presents a larger dispersion on the data than platinum, which is explained because of its large magnetic permeability value, that generates a less homogeneous gas than in the platinum case.